PENGARUH TERPAAN TAYANGAN “SUARA HATI ISTRI” DI INDOSIAR TERHADAP KECEMASAN PERNIKAHAN PEREMPUAN PRA NIKAH DI DESA SRIKANDANG - Feni Ersa Silviana; Sri Wahyuningsih (Program Studi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Baturaja, 2021)
Television is one of the mass media that is widely used by Indonesian people as a medium of information, education, and even entertainment. But not infrequently this television show affects the perception and attitude of the audience. The purpose of this study was to determine whether there was an effect of exposure to the FTV show